O índio e o seringueiro no (dis) curso de O Juruá. - Ana Claúdia de Souza Garcia (Nepan editor, 2021)
This study comes from the research entitled Textual and everyday genres: unveiling the city of Cruzeiro do Sul-Acre in the pages of the newspaper “O JURUÁ” (from 1953 to 1962), the work presented in the Master’s Course of the Graduate Program in Letters: Language and Identity, of the Federal University of Acre. This research opened a range of possibilities for analysis in the field of language. In this perspective, the discursive genres, considered as fundamental elements in the process of construction of the utterance and, consequently, of the discourse, were studied more specifically, in the light of Bakhtinian thinking, with contributions from Marcuschi (2008). This article, therefore, deals with an analysis of some texts of the newspaper O Juruá, relating the notion of gender of discourse with the production of meanings around two themes: the Indian and the rubber tapper.